Amphibians from the litoranean dunes of northern Piauí State, Brazil - Silva, Guilherme R. da; Santos, Clarenice L. dos; Alves, Margareth R.; Sousa, Suzy D. V. de; Annunziata, Bruno B. (SITIENTIBUS série Ciências Biológicas, 2007)
The northern Piauí is characterized by two main physiognomies, the Cerrado and the Caatinga environments, and by transitional habitats comprised mainly by dunes. This research was carried out between December 2005 and April 2007, and aimed at surveying anurans in the sand dunes of the municipality of Ilha Grande, Piauí State. Fourteen anurans species were registered, comprising five families. We increased the geographical distribution of Chaunus granulosus, C. jimi, Scinax x-signatus, Phyllomedusa nordestina, Physalaemus albifrons, Pleurodema diplolister, Leptodactylus pustulatus, and L. vastus on Piauí State. Dendropsophus nanus, Elachistocleis ovalis, Hypsiboas raniceps, Leptodactylus fuscus, L. ocellatus, and Pseudopaludicola mystacalis were registered for the first time in Piauí State.